2019
DOI: 10.2478/jesr-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Deviant Behaviour in Secondary School and its Impact on Students’ Learning

Abstract: Students come to school to acquire knowledge, skills, positive behaviour and values for good citizenship. Students learning become more effective and meaningful when the classroom and school environment is calm and devoid of distractions. This study examined deviant behaviour in schools and how it impacts on students’ learning The study drew its sample from a population of public secondary schools in Edo State, Nigeria. The sample comprised 500 teachers selected through random sampling techniques from twenty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Furthermore, Asiyai (2019) in her study of deviant behavior among high school students in Nigeria, which included 'examination malpractices, found that students in urban schools engaged more in deviant behavior than their counterparts in rural schools. Be that as it may, there are findings from some previous studies that the academic achievement scores of students in schools located in towns are better than those of students in villages (such as (Adeyeye, 2017;Farooq, Chaudhry, Shafiq, & Berhanu, 2011;Manley, 2018;Sumi, Jahan, Rahman, Seddeque, & Hossain, 2021)).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Asiyai (2019) in her study of deviant behavior among high school students in Nigeria, which included 'examination malpractices, found that students in urban schools engaged more in deviant behavior than their counterparts in rural schools. Be that as it may, there are findings from some previous studies that the academic achievement scores of students in schools located in towns are better than those of students in villages (such as (Adeyeye, 2017;Farooq, Chaudhry, Shafiq, & Berhanu, 2011;Manley, 2018;Sumi, Jahan, Rahman, Seddeque, & Hossain, 2021)).…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of Ibn Khaldun to knowledge spread across several fields of specialization (Asiyai, 2019). With respect to the foundation of the science of civilization, otherwise known as al-umran, Fahiri (2001) and Musthafa, (2015) argues that Ibn Khaldun had postulated that human beings evolved from 'the world of the monkeys' via a broadening progression that gives rise to the multiplication of 'species' before the discovery of the specific features of evolution.…”
Section: Contributions Of Ibn Khaldun To Knowledge: An Overviewmentioning
confidence: 99%
“…It could be regarded as an effectiveness in accomplishing statutory tasks assigned to an individual (employee) in a functional organization. Issues of principals' job performance in public secondary schools in Nigeria have attracted diverse concern from scholars due to the poor quality of administrative effectiveness observed which often than not is believed to be responsible for the rising level of students' deviant tendencies (Akomolafe, 2012;Asiyai, 2019); teachers' attrition (Alabi, 2011); teachers job dissatisfaction; and poor quality of education outcome. More worrisome is that studies have shown that most of the schools lack basic school plants that are essential in the actualization of secondary education goals.…”
Section: Introductionmentioning
confidence: 99%